Soil and Rock Mechanics Investigations for the Assessment of Strata Behaviour of an Opencast Coal Mine - D.N. Sharma; Ziaullah Shareef; K.K. Sharma (Global Journal of Earth Science and Engineering, 2015)
Abstract: The Singareni Collieries Company Limited (SCCL) planned for deepening the Opencast projects from the present depth of 250m to 400m. For successful operation and forecasting of strata behaviour in pre-mining was recognized. In this direction, SCCL had tie-up with CSIRO, Australia to work jointly, with a lead research provider. As part of these studies, to meet the requirement of generating needy data to conduct Numerical Modelling, extensive program was organized to take up different Physico Mechanical Properties (PMP) tests. In light of this, different tests suggested were taken up in SCCL and NIRM laboratories. The data thus generated were analyzed statistically to make use of the same for Numerical Modelling by CSIRO, Australia. The data generated during the course of organizing different tests, are synthesized and discussed in this paper. The paper deals with the methodology evolved in generation of desired soil and Rock Mechanics data to assess the stability of pit slopes, internal dump and OB dumps.